2008
DOI: 10.1093/rheumatology/ken457
|View full text |Cite
|
Sign up to set email alerts
|

Febuxostat in the treatment of gout: 5-yr findings of the FOCUS efficacy and safety study

Abstract: Long-term treatment with febuxostat resulted in durable maintenance of sUA < 6.0 mg/dl for most subjects. There was nearly complete abolition of gout flares in patients completing the study. Baseline tophi resolved in a majority of subjects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
147
0
9

Year Published

2012
2012
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 229 publications
(163 citation statements)
references
References 26 publications
7
147
0
9
Order By: Relevance
“…The proportion of patients with gout flares requiring treatment declined over 52 weeks, similar to that observed in other studies with febuxostat or allopurinol 5, 6, 8. Longer‐term treatment may be needed to further reduce gout flares, as well as to dissolve baseline tophi, particularly to demonstrate treatment effect differences 24, 25.…”
Section: Discussionsupporting
confidence: 74%
“…The proportion of patients with gout flares requiring treatment declined over 52 weeks, similar to that observed in other studies with febuxostat or allopurinol 5, 6, 8. Longer‐term treatment may be needed to further reduce gout flares, as well as to dissolve baseline tophi, particularly to demonstrate treatment effect differences 24, 25.…”
Section: Discussionsupporting
confidence: 74%
“…Clinical trial data comparing allopurinol with febuxostat were available over variable time periods (from 6 months up to 60 months). 5,6,13,21 The first-year probabilities used in the economic model were pooled estimates based on information from 2 randomized controlled trials (RCTs) for allopurinol and febuxostat: the Febuxostat versus Allopurinol Control Trial (FACT; n = 762) observed over 52 weeks and the 28-week Allopurinol and Placebo-controlled Efficacy study of febuXostat (APEX). 6,13 This approach was appropriate because the 2 clinical trials, FACT and APEX, used identical patient populations and efficacy and safety endpoints.…”
Section: ■■ Methodsmentioning
confidence: 99%
“…5 Additional long-term data for urate-lowering and clinical efficacy and safety were obtained from a previously published study and the 5-year Febuxostat Open-label Clinical Trial of Urate-Lowering Efficacy and Safety (FOCUS) extension study. 17,21 Since the mortality rates across both treatment arms did not significantly differ, it was assumed that the transition probabilities to death were identical for both treatment arms. 24 The model was designed from the health care payer perspective in the United States.…”
Section: Resource Use and Base-case Undiscounted Cost Values And Rangmentioning
confidence: 99%
“…However, there are no active or completed clinical trials evaluating the use of febuxostat for this indication (57). Febuxostat does seem to be efficacious in the treatment of hyperuricemia associated with gout (58,59). Because its mechanism of action is similar to that of allopurinol, febuxostat would not be expected to decrease the accumulation of xanthine or the risk for xanthine stone formation.…”
Section: Febuxostatmentioning
confidence: 99%